Pedagogical Conditions for the Formation of Students' Clinical Thinking (Eurasian Medical Research Periodical, 2022)
This article discusses the system for the formation of clinical thinking in future doctors in the process of medical education, the factors influencing this process. At the same time, the views of clinicians on this problem were also analyzed. The methods of forming clinical thinking among students and the basic requirements that must be followed in the process of their use are noted.